Carbonization Tuned Core‐Shell Fe3O4@C Nanostructures with Enhanced Electromagnetic Wave Absorption - Jiang Guo; Yukun Sun; Xu Li; Guangmin Zhao; Mohamed H. Helal; Duo Pan; Hamdy Khamees Thabet; Wenling Wu; Waras Abdul; Salah M. El‐Bahy; Hassan Algadi; Zhanhu Guo; et al. (Advanced Materials Interfaces, 2025)
Abstract With the advent of high‐power electronic devices, communication satellites, and military radar systems, electromagnetic (EM) waves have caused significant pollution. In this work, hollow Fe3O4@C (H‐FO@C) composites are synthesized by employing an in situ polymerization and carbonization treatment. Effects of carbonization temperature on electromagnetic wave absorption of core‐shell structured H‐FO@C composites are symmetrically analyzed, and the impedance matching and attenuation ability are improved significantly by controlling carbonization temperature. The reflection loss (RL) and effective absorption bandwidth (EAB) of H‐FO@C composites carbonized at 650 °C are improved to −51.85 dB and 5.36 GHz (thickness 2.1 mm), respectively. When the thickness of composites increases from 2.1 to 2.4 mm, the EAB reaches 6.24 GHz. According to CST Studio Suit, the radar cross section (RCS) reduction value can be 24.26 dB m2 for H‐FO@C composites. Both experiment and simulation results confirm that the H‐FO@C composites possess excellent EWA performance. This work provides a new way for advancing EWA materials.